2014
DOI: 10.1144/sp401.20
|View full text |Cite
|
Sign up to set email alerts
|

Age relationships of the Rembrandt basin and Enterprise Rupes, Mercury

Abstract: The Rembrandt basin is the largest well-preserved impact feature in the southern hemisphere of Mercury. Its smooth volcanic infill hosts wrinkle ridges and graben, and the entire basin is cross-cut by the Enterprise Rupes scarp system. On the basis of the Model Production Function crater chronology, our analysis shows that the formation of the Rembrandt basin occurred at 3.8±0.1 Ga during the Late Heavy Bombardment, consistent with previous studies. We also find that the smooth plains interior to the basin wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…The N (10) values we report here for these nine sites are similar to those for the largest expanses of effusive volcanic deposits on Mercury—the NSP, Caloris Planitia and the smooth plains exterior to Caloris, and the Rembrandt interior plains [ Fassett et al ., ; Head et al ., ; Strom et al ., ; Denevi et al ., ; Ferrari et al ., ; Ostrach et al ., ]—as well as for smaller units, including smooth plains near Rudaki crater [ Denevi et al ., ] (Tables and S1). Further, our results for the Beethoven and Faulkner sites resemble N (10) values for those deposits reported earlier [e.g., Denevi et al ., ; Whitten et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N (10) values we report here for these nine sites are similar to those for the largest expanses of effusive volcanic deposits on Mercury—the NSP, Caloris Planitia and the smooth plains exterior to Caloris, and the Rembrandt interior plains [ Fassett et al ., ; Head et al ., ; Strom et al ., ; Denevi et al ., ; Ferrari et al ., ; Ostrach et al ., ]—as well as for smaller units, including smooth plains near Rudaki crater [ Denevi et al ., ] (Tables and S1). Further, our results for the Beethoven and Faulkner sites resemble N (10) values for those deposits reported earlier [e.g., Denevi et al ., ; Whitten et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…In the southern hemisphere, the plains interior to the Rembrandt basin form the largest volcanic deposit. Crater size–frequency analyses have shown that the NSP and the Caloris and Rembrandt interior plains were emplaced at around 3.7 Ga [ Fassett et al ., ; Head et al ., ; Strom et al ., ; Denevi et al ., ; Ferrari et al ., ; Ostrach et al ., ] for many of the published chronology models for Mercury [e.g., Marchi et al ., ], including the model of Le Feuvre and Wieczorek [] that incorporates the effects of a porous megaregolith. Further, the areal density of impact craters for an additional large smooth plains deposit on Mercury—southeast of the Rachmaninoff basin, near Faulkner crater—is comparable to those for the NSP and the Caloris interior plains [ Fassett et al ., ; Denevi et al ., ; Whitten et al ., ; Ostrach et al ., ], implying that this additional unit is similar in age.…”
Section: Introductionmentioning
confidence: 99%
“…Smooth plains in the interior of Rembrandt, mapped on the basis of morphology and spectral characteristics, are interpreted to be volcanic in origin and are the oldest expanse of smooth plains on Mercury with an N (20) value of 45 ± 12 [ Denevi et al , ]. Ferrari et al [] estimated ages for Rembrandt (~3.8 Ga) and the interior smooth plains (~3.6 Ga) using a model production function method, comparable to previous estimates [ Watters et al , ; Fassett et al , ; Denevi et al , ].…”
Section: Timing Of Deformationmentioning
confidence: 99%
“…Ferrari et al [] speculated that the formation of Enterprise Rupes predates the formation of the Rembrandt basin. They suggested that postscarp formation of the basin perturbed the stress field and reoriented the strike of a branch of the fault as it grew within the new basin.…”
Section: Timing Of Deformationmentioning
confidence: 99%
“…The time-stratigraphic relationship between the 715 km-diameter Rembrandt impact basin and the Enterprise Rupes scarp system, which extends for over 800 km across the surface of Mercury, is the focus of the work by Ferrari et al (2014). These authors find that the Rembrandt basin formed at about 3.8 Ga, with resurfacing of its interior by volcanic smooth plains occurring within 100 -300 myr after basin formation.…”
Section: R C Ghail and L Wilsonmentioning
confidence: 99%